Kajian Kemampuan Pemecahan Masalah Matematis Dan Berpikir Kritis Matematis Siswa Pada Persoalan Sistem Persamaan Linier Dua Variabel Dalam Konteks Kebudayaan - Aneu Pebrianti; Elia Nurindah Sari; Dori Lukman Hakim; Dani Firmansyah; Fahmi Nugraha heryanto; Ebenezer Bonyah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2026)
The objective of this study is to assess the mathematical problem-solving and critical thinking skills of students in the subject of Two-Variable Linear Equation Systems (SPLDV) within the context of batik culture. The research employed a descriptive qualitative approach, supplemented by rudimentary quantitative data, in a study of 36 eighth-grade students at a junior high school in Karawang Regency. The research instruments employed included a culture-based SPLDV written test, interviews, observations, and documentation. The analysis of mathematical problem-solving skills is referred to as Polya's stages, while mathematical critical thinking skills are analyzed based on Ennis' indicators. The findings indicate that students' mathematical critical thinking skills remain deficient, particularly in the domains of making conjectures, developing and evaluating arguments, and verifying solutions through substitution and graphical representation. Concurrently, mathematical problem-solving aptitudes indicated that the capacity to comprehend problems was in the adequate range, the aptitude to formulate strategies was in the satisfactory range, the aptitude to execute strategies was suboptimal, and the aptitude to verify was the least proficient aspect. These findings suggest a necessity for educational approaches that prioritize the cultivation of procedural, evaluative, and reflective skills by leveraging meaningful cultural contexts.